Accelerated wet aging study of flax-reinforced UPR composites - Wang Qiuhong; Ji Yingchao; Wang Ying; Li Hong (Functional Materials, 2016)
The plain and satin fabrics were weaved with 66.67 tex flax yarns. With flax fabric as the reinforcement and Unsaturated Polyester Resin (UPR) as the matrix, composites of two, three and four layers were fabricated respectively by the Vacuum Assisted Resin Infusion (VARI) technique. The wetting capability of the composites was tested firstly. The wetting rate illustrated that the weight of the composites were fast increased when immersed in the water. And the impact property of the composites after saturated in the water for different duration time was tested. The impact property of the four-layer plain fabrics composites was decreased after immersing in water for one-, two-and three-month. After reaching the minimum impact property, the impact property was found recovered after six-month water immersion. For the two- and three-layer plain fabrics specimens, the impact property was increased in the whole experiment process. For the two-layer satin fabrics specimens, the impact property was increased initially for one-month, decreased for two-month and three-month and increased instead for six-month after water immersion. Scanning electron microscopy (SEM) confirmed that the enhancement effect of the wet flax fibre may be over-weighed by the degradation effect of the materials. The results indicated that the materials had experienced some forms of physical damage and/or chemical degradation. The weakening of bonding between fibre and matrix and softening of matrix material were also reasons of the decreased composite property.